2022
DOI: 10.1371/journal.pone.0267311
|View full text |Cite
|
Sign up to set email alerts
|

Towards skin-acetone monitors with selective sensitivity: Dynamics of PANI-CA films

Abstract: Most research aimed at measuring biomarkers on the skin is only concerned with sensing chemicals in sweat using electrical signals, but these methods are not truly non-invasive nor non-intrusive because they require substantial amounts of sweat to get a reading. This project aims to create a truly non-invasive wearable sensor that continuously detects the gaseous acetone (a biomarker related to metabolic disorders) that ambiently comes out of the skin. Composite films of polyaniline and cellulose acetate, exhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…In conclusion, we have shown that energy cost scales non-linearly with joint torque and predicts bilateral limb force sharing and the same exponent is applicable to muscle force sharing. Such metabolic cost models, when generalized to each joint or muscle, may be used in whole body biomechanical simulations for predictions of movement behavior as well as potentially for real-time metabolic monitoring [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we have shown that energy cost scales non-linearly with joint torque and predicts bilateral limb force sharing and the same exponent is applicable to muscle force sharing. Such metabolic cost models, when generalized to each joint or muscle, may be used in whole body biomechanical simulations for predictions of movement behavior as well as potentially for real-time metabolic monitoring [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the host response of a subject-in this case the gases emitted from cells in the case of infection by a virus-a novel sensor system/breath tester for COVID-19 which produced a breath print for the infection by "smelling" a single exhaled breath was also demonstrated [6]. At the same time, there are chemo-mechanical actuators and resistors for sensing gases emitted from skin cells [7]. These breakthroughs have opened the way to explore fundamentally novel approaches to safeguard the environment, protect public health and individual well-being through the processing of living sensor systems that detect pathogens rapidly, as described next.…”
Section: How To Design Living Cell Sensorsmentioning
confidence: 99%
“…A good sensor exhibits key factors that contribute to its performance, including sensitivity, specificity, resolution, repeatability, and response time [4][5][6]. P-TENG technology, with its compatibility with numerous piezoelectric and triboelectric materials, enables the development of tailored sensors that embody these characteristics [7].…”
Section: Introductionmentioning
confidence: 99%